Analyzing Middle School Students’ Use of the ARTEMIS Digital Library - June Abbas; Cathleen Norris; Elliot Soloway (2011)

Middle school students's use of the ARTEMIS digital library - June Abbas; Cathleen Norris; Elliot Soloway (ACM/IEEE Joint Conference on Digital Libraries (JCDL '02), 2002)
Research into student use of scaffolding features and representation issues encountered while using the ARTEMIS Digital Library is discussed. Research agenda, methods, preliminary findings, and future research directions are presented. Preliminary findings indicate that students exhibit some commonalities in their patterns of system and scaffold use. © 2001 IEEE.
Keywords: ARTEMIS